Empirical Evaluation of Design Level Metrics for Aspect Oriented Business Process Execution Language in SOA - S, Senthil Velan; M, Sam Jaffray (International Journal of Engineering and Technology, 2018)
Service Oriented Architecture (SOA) facilitates seamless application integration through standards-based predefined web services. During integration, Business Process Execution Language (BPEL) plays a vital role in composing existing Web Services thereby achieving a service based workflow model.Â Â  Due to frequently changing business requirements, it becomes very much essential for an SOA application to have the capability to dynamically bind with an alternate service rather than statically fixing the services in a given composition. However, BPEL lacks support for the run-time inclusion of a new Web Service or functionality. Aspects overcome this limitation by providing support to independently encapsulate the cross-cutting functionalities by separating them from the core business logic. Using AOP, it is possible to achieve dynamic binding in web service composition. To illustrate the embedding of AOP constructs into a BPEL process, this paper implements a case study on distributed e-HealthCare system. Further, two core design level properties namely, cohesion and coupling have been measured and the impact of introduction of AO into a composed BPEL process has also been discussed. Empirical evaluation of the design level properties shows that cohesion improves by the introduction of AOP in BPEL.
Keywords: AOSD; SOA; BPEL; Software Design Metrics; Cohesion; Coupling